Effect of Surface Morphology of Poly(ϵ‐caprolactone) Scaffolds on Adipose Stem Cell Adhesion and Proliferation. Issue 1 (December 2013) - Diban, Nazely; Haimi, Suvi P.; Bolhuis‐Versteeg, Lydia; Teixeira, Sandra; Miettinen, Susanna; Poot, André A.; Grijpma, Dirk W.; Stamatialis, Dimitrios; Lendlein, Andreas; Neffe, Axel T.
Summary The effect of the surface morphology of flat poly(ϵ‐caprolactone) (PCL) scaffolds on human adipose stem cell (hASC) adherence and proliferation was studied. During fabrication of the scaffolds by phase inversion, the employment of different non‐solvents (water (W), ethanol (EtOH) or isopropanol (IPA)) led to distinct surface morphologies. It was found that PCL scaffolds fabricated using IPA as a non‐solvent had a higher roughness and porosity compared to the other groups. Moreover, during culturing of hASCs under static conditions, best cell attachment, spreading and growth were observed on the PCL scaffold. Our results show the potential of PCL scaffolds prepared using IPA as a non‐solvent for especially soft tissue engineering applications.